2014
DOI: 10.1536/ihj.13-216
|View full text |Cite
|
Sign up to set email alerts
|

Change in Carotid Intima-Media Thickness in a High-Risk Group of Patients by Intensive Lipid-Lowering Therapy With Rosuvastatin

Abstract: SummaryCarotid intima-media thickness (IMT), a measure of atherosclerosis, is modulated by multiple risk factors. Accordingly, comprehensive control of risk factors is indispensable for management of atherosclerosis. In this study, as a posthoc analysis of the JART Study we planned two analyses. In the main analysis, we evaluated the effect of intensive lipidlowering therapy with rosuvastatin on carotid IMT in high-risk patients. We also evaluated effi cacy in the presence or absence of each risk factor using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…40) In addition, statins slower the progression of CIMT. 41,42) Shimizu, et al 43) reported that ARB completely prevented calcification. These data suggest that statins and ARBs, and possibly ACEIs, or any combinations thereof, may reduce the serum levels of OPG and thus modulate the progression of CIMT.…”
Section: Elevated Opg Levels and Coronary Artery Diseases And Cimtmentioning
confidence: 99%
“…40) In addition, statins slower the progression of CIMT. 41,42) Shimizu, et al 43) reported that ARB completely prevented calcification. These data suggest that statins and ARBs, and possibly ACEIs, or any combinations thereof, may reduce the serum levels of OPG and thus modulate the progression of CIMT.…”
Section: Elevated Opg Levels and Coronary Artery Diseases And Cimtmentioning
confidence: 99%
“…2,3) Statins have also been shown to slow the progression or even promote the regression of coronary atherosclerosis. [4][5][6][7][8][9][10][11] Despite the established efficacy of statins, however, the attainment of low-density-lipoprotein cholesterol (LDL-C) levels recommended by the guidelines is often suboptimal. 12) Ezetimibe is a novel cholesterol absorption inhibitor that prevents the absorption of dietary and biliary cholesterol from the small intestine.…”
mentioning
confidence: 99%
“…Also, the present participants received various drugs for the treatment of diabetes, hypertension and dyslipidemia during the study period. Head‐to‐head clinical trials have shown that drugs differ in their effects on the progression of CIMT . Furthermore, the contributions of cardiovascular risk factors to the progression of atherosclerosis might differ among study participants.…”
Section: Discussionmentioning
confidence: 99%